1995
DOI: 10.1111/j.1365-2265.1995.tb02689.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth and cardiovascular effects of high dose growth hormone therapy in idiopathic short stature

Abstract: High dose (40 IU/m2/week) r-hGH treatment of children with idiopathic short stature resulted in a greater short-term acceleration in growth rate than 'standard' dose therapy without an excessive advance in skeletal maturity and probably represents the optimal growth promoting dose for short, normally growing children. Whether continued high dose r-hGH therapy increases final height requires further study. Left ventricular morphology and function remained within the normal range during r-hGH therapy but regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…GVSDS showed a significant increase in GHtreated children at 1 year in prepubertal children (p < 0.001) 40 and pubertal children (p < 0.05) 41 compared with untreated controls, and at 6 months in prepubertal children compared with those receiving placebo (p < 0.0001).…”
Section: Gvsdsmentioning
confidence: 92%
See 3 more Smart Citations
“…GVSDS showed a significant increase in GHtreated children at 1 year in prepubertal children (p < 0.001) 40 and pubertal children (p < 0.05) 41 compared with untreated controls, and at 6 months in prepubertal children compared with those receiving placebo (p < 0.0001).…”
Section: Gvsdsmentioning
confidence: 92%
“…In the Soliman trial, 23 a change in HtSDS was also shown after 1 year of GH treatment in prepubertal children, from -2.55 ± 0.5 to -1.7 ± 0.45 in the GH-treated group, compared with a change from -2.8 ± 0.96 to -2.6 ± 0.9 in untreated controls (p < 0.05). The Barton trial 40 testing prepubertal children found no significant differences in HtSDS between treated and untreated children after 1 year, even when considering a high dose of GH (40 IU/m 2 per week). In the Volta trial, 41 a significant change in HtSDS from baseline was reported after 1 year of GH treatment in pubertal children in whom HtSDS changed from -2.2 ± 0.2 to -1.7 ± 0.2 (p < 0.05), compared with no change in untreated controls or those children receiving LHRHa.…”
Section: Htsdsmentioning
confidence: 96%
See 2 more Smart Citations
“…Several randomized trials have demonstrated that GH administration accelerates growth in the short term (6)(7)(8). Furthermore, most, but not all, nonrandomized long-term studies suggest that GH increases adult height of children with idiopathic short stature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Efficacy Of Gh Treatment In Issmentioning
confidence: 99%